Impact of glucose-6-phosphate dehydrogenase deficiency on the pathophysiology of cardiovascular disease - Hecker, Peter A. (American Physiological Society, 2013)
Glucose-6-phosphate dehydrogenase (G6PD) catalyzes the rate-determining step in the pentose phosphate pathway and produces NADPH to fuel glutathione recycling. G6PD deficiency is the most common enzyme deficiency in humans and affects over 400 million people worldwide; however, its impact on cardiovascular disease is poorly understood. The glutathione pathway is paramount to antioxidant defense, and G6PD-deficient cells do not cope well with oxidative damage. Limited clinical evidence indicates that G6PD deficiency may be associated with hypertension. However, there are also data to support a protective role of G6PD deficiency in decreasing the risk of heart disease and cardiovascular-associated deaths, perhaps through a decrease in cholesterol synthesis. Studies in G6PD-deficient (G6PDX) mice are mixed and provide evidence for both protective and deleterious effects. G6PD deficiency may provide a protective effect through decreasing cholesterol synthesis, superoxide production, and reductive stress. However, recent studies indicate that G6PDX mice are moderately more susceptible to ventricular dilation in response to myocardial infarction or pressure overload-induced heart failure. Furthermore, G6PDX hearts do not recover as well as nondeficient mice when faced with ischemia-reperfusion injury, and G6PDX mice are susceptible to the development of age-associated cardiac hypertrophy. Overall, the limited available data indicate a complex interplay in which adverse effects of G6PD deficiency may outweigh potential protective effects in the face of cardiac stress. Definitive clinical studies in large populations are needed to determine the effects of G6PD deficiency on the development of cardiovascular disease and subsequent outcomes.